Digital Achievement Motivation Scale for Mathematics Learning: Validity, Reliability, and Micro Testing Evidence - Suciati Rahayu Widyastuti (CV FOUNDAE, 2025)
Achievement motivation plays a crucial role in students' success in mathematics learning, yet valid and practical measurement instruments are still limited, especially those that utilize digital questionnaire platforms. This study aims to develop an Achievement Motivation Scale for High School Students in Mathematics Learning using a digital questionnaire platform. The research method used is the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. A total of 30 items were constructed from five motivational dimensions and validated by 3 experts, resulting in 24 valid items (86.7%) and six revised items. Usability testing involving three Information Technology experts, three teachers, and three students yielded average scores of 73%, 93.3%, and 86.7%, respectively, indicating the instrument is user-friendly and well-received. Field testing with 57 students revealed 14 items met the discrimination index (r ≥ 0.30). Exploratory factor analysis showed factor loadings between 0.40–0.85, supporting construct validity. Reliability testing using Cronbach's Alpha yielded 0.89, indicating high internal consistency. Thus, 14 items were declared valid, reliable, and practical for measuring achievement motivation in mathematics learning using a digital platform